Plant selenium accumulation and the rhizosphere effect - Alford, Élan Reine, author; Paschke, Mark W., advisor; Binkley, Dan, committee member; Borch, Thomas, committee member; Pilon-Smits, Elizabeth, committee member; Stromberger, Mary, committee member (Colorado State University. Libraries, 2011)
To view the abstract, please see the full text of the document.
Keywords: phytoremediation; legume; nodulation; Astragalus; biosolids